2021
DOI: 10.1590/1413-812320212612.32802020
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do Programa Academia da Saúde sobre a mortalidade por Hipertensão Arterial Sistêmica no estado de Pernambuco, Brasil

Abstract: Resumo O objetivo deste artigo foi avaliar o impacto do Programa Academia da Saúde sobre a mortalidade por Hipertensão Arterial Sistêmica no estado de Pernambuco, Brasil. Este estudo quase-experimental configura-se como uma avaliação de impacto de políticas públicas, desenvolvida através da aplicação do método do Pareamento por Escore de Propensão, nos anos de 2010 e 2017. Utilizou-se dados socioeconômicos, demográficos e epidemiológicos dos 89 municípios que implantaram o programa (tratados) e de outros 52 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…The current study identified that the presence of the HGP reduces expenses with hospitalizations for stroke. Other studies have already evaluated the impact of the HGP in Pernambuco and found that the program reduced expenses with hospital admissions for cerebrovascular diseases [14] and mortality from systemic arterial hypertension [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study identified that the presence of the HGP reduces expenses with hospitalizations for stroke. Other studies have already evaluated the impact of the HGP in Pernambuco and found that the program reduced expenses with hospital admissions for cerebrovascular diseases [14] and mortality from systemic arterial hypertension [21].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence points out that health promotion programs can mitigate the occurrence of cases and expenses with hospitalizations for stroke [13,14], and that the HGP was effective in increasing the level of physical activity of the population [20] and reducing the mortality from arterial hypertension [21]. However, the relationship between the implementation of the program and public spending on health is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, entre adultos brasileiros, a HAS acomete 32,6% da população e é especialmente prevalente entre idosos, ocorrendo em 60% dos indivíduos acima de 60/65 anos além de estar relacionada com 0,87 óbitos a cada 10 mil adultos no país, revelando seu impacto 4 .…”
Section: Introductionunclassified